SPIRITUALITAS JEMAAT DAN KETAHANAN IMAN DI MASA KRISIS SOSIAL: PERSPEKTIF TEOLOGI PASTORAL - Tantri Yulia; Simon Simon; Tjutjun Setiawan (Manna Rafflesia, 2025)
Social crises such as pandemics, social conflicts, and economic instability affect the strength of community faith. The purpose of this paper is to investigate how congregational spirituality can help faith resilience in the midst of crisis using a pastoral theological approach. The main question posed in this study is how spirituality and church community build faith resilience in times of social crisis? The method used is a descriptive qualitative study with a theological-pastoral approach, utilizing literature review and contextual analysis. The findings of this study indicate that various spiritual practices, such as prayer and fellowship, as well as involvement in the church community, are highly influential in strengthening the faith of the congregation amidst crisis situations. However, obstacles such as a lack of discipleship and community fragmentation were also found. Therefore, the church must be present contextually and actively to strengthen the faith of the people during the current crisis.